High Responsivity of InP/InAsP Nanowire Array Broadband Photodetectors Enhanced by Optical Gating - Karimi, Mohammad; Zeng, Xulu; Witzigmann, Bernd; Samuelson, Lars; Borgstrom, Magnus T.; Pettersson, Hakan (Nano Letters, 2019)
High-performance photodetectors operating in the near-infrared (0.75-1.4 μm) and short-wave infrared (1.4-3.0 μm) portion of the electromagnetic spectrum are key components in many optical systems. Here, we report on a combined experimental and theoretical study of square millimeter array infrared photodetectors comprising 3 million n+-i-n+ InP nanowires grown by MOVPE from periodically ordered Au seed particles. The nominal i-segment, comprising 20 InAs0.40P0.60 quantum discs, was grown by use of an optimized Zn doping to compensate the nonintentional n-doping. The photodetectors exhibit bias- and power-dependent responsivities reaching record-high values of 250 A/W at 980 nm/20 nW and 990 A/W at 532 nm/60 nW, both at 3.5 V bias. Moreover, due to the embedded quantum discs, the photoresponse covers a broad spectral range from about 0.70 to 2.5 eV, in effect outperforming conventional single InGaAs detectors and dual Si/Ge detectors. The high responsivity, and related gain, results from a novel proposed photogating mechanism, induced by the complex charge carrier dynamics involving optical excitation and recombination in the quantum discs and interface traps, which reduces the electron transport barrier between the highly doped n+ contact and the i-segment. The experimental results obtained are in perfect agreement with the proposed theoretical model and represent a significant step forward toward understanding gain in nanoscale photodetectors and realization of commercially viable broadband photon detectors with ultrahigh gain.
CRIS-Team Scopus Importer:2021-06-11
Keywords: discs-in-nanowires; infrared photodetectors; interface traps; nanowire array photodetectors; Nanowires; optical gain; photogating; quantum discs